PENGARUH KOMPETENSI KEWIRAUSAHAAN DAN ETOS KERJA TERHADAP KINERJA PELAKU UMKM DI KOTA TANGERANG - Pandji Pratopo; Lena Erdawati; Atik Atikah; Yanthi Metri Gunawan (Universitas Muhammadiyah Tangerang, 2021)
The purpose of this study was to determine the effect of entrepreneurial competence and work ethic partially and simultaneously (jointly) on the performance of UMKM players in Tangerang City, studying in Tanah Tinggi Central Market, Tangerang City. This study uses an associative method with a quantitative approach. Sampling as many as 52 people, with the Slovin method. Data collection techniques and tools are literature study, observation, and questionnaires or questionnaires. The data analysis technique used is descriptive analysis to determine the description of respondents' responses and data distribution, while inferential statistics are used for hypothesis testing. Data processing is assisted by Microsoft Excel and SPSS software version 25. The results of hypothesis testing show that: The contribution of competence and work ethic to the performance of UMKM players is 54.6%, while the remaining 45.4% is influenced by other variables not examined. The higher the competency value and work ethic at the same time at a certain value, then the high the competency value and work ethic value make the performance value of UMKM actors increase at a certain value as well. Hypothesis testing proves that there is a significant effect of entrepreneurial competence and work ethic partially or simultaneously (jointly) on the performance of UMKM players in the Main Market of Tangerang City. The most dominant influence on the performance of UMKM actors seen from the coefficient of determination is the entrepreneurial competence variable. A person who has a high work ethic and entrepreneurial competence will provide an increase in his performance as a business hammer.